Integrasi Nilai-Nilai Moderasi Beragama Dalam Mengembangkan Kurikulum Pendidikan Agama Islam - Nina Ayu Puspita Sari; M. Nasor; Rendra Nasrul Rifai; Esen Pramudya Utama; Raicha Oktafiani (Journal on Education, 2024)
This exploration expects to make sense of the reconciliation of strict balance in fostering the Islamic strict training educational program. This sort of examination is subjective with a library research approach. Research information comprises of information on strict control, educational plan improvement, PAI material from essential sources as pertinent books and diaries. Information assortment methods are completed utilizing documentation. The scientists' information sources were gotten from books and diaries about strict control, educational plan improvement, PAI materials. Information investigation utilizes Content Examination. In view of the portrayal over, the creator reaches the determination that strict control is an "pressing" task for instructive foundations, particularly Islamic instructive organizations. The ascent of outrageous peculiarities in religion today opens our psyches and hearts as Muslims to the significance of rehearsing Islam like the Prophet Muhammad SAW. The showing values brought by him have essentially become Islamic lessons, however after some time, the upsides of Islamic lessons have moved, combined with the ongoing current of globalization. Endeavors to coordinate the upsides of strict balance into PAI subjects are the underlying venturing stone to framing an age of moderate Indonesian Muslims, becoming trailblazers of harmony and carrying out the case of Rasulullah SAW as a gift for the whole universe. It is vital to fabricate a learning environment to help this combination, and it is trusted that it will create understudies who have confidence and dedication to Allah SWT, have honorable person, are peaceful, open minded, and regard contrasts which are a need among humankind